The traditional specialities guaranteed scheme under European Union law - Kapała, Anna (Przegląd Prawa Rolnego, 2023)
The aim of this study was to determine the legal nature and scope of protection of traditional specialities guaranteed (TSGs) and, against this background, to assess whether the TSG scheme fulfils its purpose of supporting producers in marketing their products, protecting traditional production methods and advising consumers on the value-adding characteristics of these products. The results of the study have shown that producers of traditional products from a specific geographical area do not have an exclusive right to use a registered name, as a result of which the TSG scheme does not provide them with a competitive advantage and therefore does not fulfil its objective of supporting them in marketing their products. It also prejudges the difficulty of protecting traditional production methods throughout the EU, whereas, when the registered name is reserved and official controls of the use of the name are mandatory, the TSG scheme is credible and provides consumers with reliable ( albeit not entirely clear) information on the added value of the traditional product.